INTERPRETATION OF RELIGIOUS SCRIPTURES FROM ASIAN CONTEXT - Kadankavil, Thomas (Journal of Dharma, 2005)
The thrust of this essay is to explore the possibilities of evolving a new universal hermeneutics for the Sacred Scriptures of world religions, giving importance to the distinctive factors of the living context of the nations in which these religious texts have been accepted as sacred. This may lead us to the distinction of a restrictive sense of the text related to the author, the cultural background, the life style and the self-training of the listeners, the exigencies of the time which urged the prophets to be very emphatic, and selective in their spiritual utterances and a significance which an interpreter identifies as having a universal appeal cutting across the barriers of place and epoch. If this assumption could be recognized as a functional hypothesis the new hermeneutics would become the meeting point of the world religions as well as the followers of these religions.